1975
DOI: 10.2134/agronj1975.00021962006700030015x
|View full text |Cite
|
Sign up to set email alerts
|

Cottonseed Density: Associated Germination and Seedling Emergence Properties1

Abstract: Recent studies have indicated that separation of cottonseed (Gossypium hirsutum L.) for improvement in seed quality should be based on seed density rather than seed size or weight. Seed density is closely related to embryo maturity and is more independent of genotype than are other seed properties. The primary objective of this study was to determine the effect of seed density on some of the processes associated with cottonseed germination and seedling establishment of several cultivars. Acid delinted seed wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
2

Year Published

1985
1985
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 5 publications
(7 reference statements)
2
26
0
2
Order By: Relevance
“…The germination (shoot emergence) of seeds of sapucaia with density ≥ 0.901g.L -1 was > 60% and it was null at density classes < 0.701 g.L -1 . The relation between seed density and germination capacity is known, and the results found here are similar, for example, to those found by Krieg and Bartee (1975), who reported that the germination of seeds of Gossypium hirsutum L. is positively related to seed density. These authors also reported that the cotton seed quality depends more on seed density than on seed size or weight, and that density is closely related to the embryo maturity status, being more independent of genotype than other seed trait.…”
Section: Discussionsupporting
confidence: 91%
“…The germination (shoot emergence) of seeds of sapucaia with density ≥ 0.901g.L -1 was > 60% and it was null at density classes < 0.701 g.L -1 . The relation between seed density and germination capacity is known, and the results found here are similar, for example, to those found by Krieg and Bartee (1975), who reported that the germination of seeds of Gossypium hirsutum L. is positively related to seed density. These authors also reported that the cotton seed quality depends more on seed density than on seed size or weight, and that density is closely related to the embryo maturity status, being more independent of genotype than other seed trait.…”
Section: Discussionsupporting
confidence: 91%
“…In several studies, genetically small seeds have been shown to have superior viability (Calero et al 1981;Nangju 1979;Singh et al 1978). Green et al (1965) (McDonald 1975), cotton (Gossypiumhirsuturn L.) (Krieg and Bartee 1975), and sorghum (Sorghum bicolor L. Moench) (Maranville and Clegg 1977) (Woodstock 1973;McDonald 1975), and the conductivity test (McDonald 1975 In exps. 1,2, and 3 the current level per seed, as measured in the single seed conductivity test (A5,{-610) (Table 3), was found to increase as seed size increased.…”
mentioning
confidence: 99%
“…Physical seed traits such as the seed index, the seed volume and seed density are all determinants of seed vigour (Ferguson and Turner, 1971;Krieg and Bartee, 1975;Minton and Supak, 1980;Leffler and Williams, 1983), and in cotton all strongly influence crop stands, growth and seed cotton yield (Minton and Supak, 1980;Hofmann et al, 1988). The seed index (the weight of 100 seeds) is related to seed cotton yield (Rahman et al, 1991), while the number of seeds per boll is recognised as the largest contributor to lint yield after the number of bolls per unit area (Worley et al, 1974(Worley et al, , 1976.…”
Section: Introductionmentioning
confidence: 99%